Vegetationslösningar och andra metoder mot stranderosion - Wallén, Paul (2008)
Today 70 percent of the world's sand beaches are under recession due to erosion. The global warming may have the effect upon the sea level increasing and the erosion increasing on the sand beaches. To save these sand beaches, the erosion must be prevented. Coast erosion shelters like gabions and sea walls are functioning extremely well to protect the land behind the sand beach, but due to the wave reflections, created in front of these so called hard erosion shelters, the erosion of the front beach is accelerated. During the last decades, artificial sand supply (beach nourishment) has been the adopted praxis. The method delays the erosion attacking shore side and also preserves the recreation area. To prevent the sand erosion, vegetation can be used. Plants that are used to prevent beach erosion are Leymus arenarius and Ammophila arenaria. Regretfully, plants do not have the ability to prevent erosion that is caused by the waves. For that reason vegetation has to be used together with beach nourishment or other method that prevent wave erosion on the sand dunes. Methods to moderate wave forces are breakwaters, sand banks created by artificial supply, etc. To make a more stable planting, coco-net can be used. To increase nitrogen in the long run, nitrogen fixing plants can be planted. The sand is poor in keeping the nutrients so when planting sand fixing plants longtime fertilizers are recommended. Arbuscular mycorrhiza has been shown to be very important when establishing sand fixing plants. Maybe arbuscular mycorrhiza could be inoculated in nursery plants for better establishment where beach restoration has been done. Because manual planting is expensive and time demanding, maybe the work can be made more effectively by producing coco-net with rhizomes from sand fixing plants, that could be easily placed and covered with sand?